Gerhard Richter's Creativity as a Transformation of Historical Genre in European Art of the Xx Century - Lvovna Panchenko, Olga (2020)
The second half of the twentieth century is marked by a high rhythm of change, which is very clearly manifested in art as a reflection of real time. In the 1960s, a new genre - a photo-painting - got its life. This genre has actively declared itself in the work of Gerhard Richter. Synthesizing paintings and photographs symbolizes the beginning of the artist's creative path. Richter's work is multidimensional and specific. This led to an increase in interest in him from the art historians and cultural experts of our time. The purpose of this article is an art history and cultural analysis of Gerhard Richter's paintings as a reflection of the transformation of twentieth-century art.The article uses the methods of discursive analysis, immersion method.